2016
DOI: 10.14295/cs.v7i1.1372
|View full text |Cite
|
Sign up to set email alerts
|

Sobrevivência, enraizamento e biomassa de miniestacas de aceroleira utilizando extrato de tiririca

Abstract: With the need of a large-scale seedling production, the application of purple nutsedge extract may represent a promising alternative, contributing to the fruit species propagation. The aim of this study was to evaluate the effects of nutsedge extract on the survival rate, rooting and biomass of acerola’s mini-cuttings. The experimental design was a completely randomized block, with a 5x2 factorial arrangement (five aqueous purple nutsedge extracts of nutsedge (0%, 25%, 50%, 75% and 100%) and two types of mini-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 13 publications
0
5
0
6
Order By: Relevance
“…Câmara et al (2016) [39] reported positive influences on the survival and sprouting rates of mini-cuttings of acerola with C. rotundus applications. Silva et al (2011) [40] also detected beneficial results using C. haspan for rooting sugarcane.…”
Section: Resultsmentioning
confidence: 99%
“…Câmara et al (2016) [39] reported positive influences on the survival and sprouting rates of mini-cuttings of acerola with C. rotundus applications. Silva et al (2011) [40] also detected beneficial results using C. haspan for rooting sugarcane.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the number of roots per minicutting, the highest score was obtained with the application of 1,000 mg L -1 of IBA, reaching a total of 19.63 (Table 2). Câmara et al (2016) mentioned that the translocation of carbohydrates from the leaves to the base of the minicutting, as well as the production of auxins and other cofactors of rooting, may have promoted stimulation to root initiation in acerola trees (Malpighia glabra L.), and such fact may have cooperated for the higher number of roots per minicutting. In this study, the minicuttings that were not treated with IBA presented the lowest number of roots, in spite of presenting higher foliar retention, together with the concentration of 1,000 mg L -1 .…”
Section: Resultsmentioning
confidence: 99%
“…An adaptation of conventional cutting is the minicutting (Moreira et al, 2017) that is used in the production of not only O. europaea cv. Barnea (Moreira et al, 2017) and Arbequina (Casarin et al, 2017;Casarin et al, 2018), but it was also tested for the production of various fruit species such as soursop (Annona muricata L.) (Figueirêdo et al, 2013), 'pitangueira'(Eugenia uniflora L.) (Peña et al, 2015), and the acerola cherry tree (Câmara et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The methodology of conducting the experiment (irrigation management) followed the one described by Lima et al (2015) by means of drainage lysimeter.…”
Section: Methodsmentioning
confidence: 99%